A novel alternative method for 3D visualisation in Parasitology: the construction of a 3D model of a parasite from 2D illustrations. - Teo, B. G.; Sarinder, K. K. S.; Lim, L. H. S. (Malaysian Society of Parasitology and Tropical Medicine, 2010)
Three-dimensional (3D) models of the marginal hooks, dorsal and ventral anchors, bars and haptoral reservoirs of a parasite, Sundatrema langkawiense Lim & Gibson, 2009 (Monogenea) were developed using the polygonal modelling method in Autodesk 3ds Max (Version 9) based on two-dimensional (2D) illustrations. Maxscripts were written to rotate the modelled 3D structures. Appropriately orientated 3D haptoral hard-parts were then selected and positioned within the transparent 3D outline of the haptor and grouped together to form a complete 3D haptoral entity. This technique is an inexpensive tool for constructing 3D models from 2D illustrations for 3D visualisation of the spatial relationships between the different structural parts within organisms.